Analisis Faktor Risiko dan Strategi Mitigasi Untuk Peningkatan Keselamatan Pelayaran di Alur Pelayaran Barat Surabaya (APBS) - Tri Wahyuni, Eni; Widodo, BL. Hetri; Rubiyanto, Aan (Majalah Ilmiah Gema Maritim, 2025)
Maritime safety is a paramount priority in sea transportation, particularly in shipping lanes (waterways) often characterized by dimensional constraints, high traffic density, and navigational complexity. This study aims to identify and analyze the primary factors contributing to maritime accidents (such as collisions, groundings, or fires) within a specified shipping lane (e.g., the Surabaya Western Shipping Lane/APBS or the Sunda Strait).Utilizing a mixed-methods approach combining qualitative and quantitative analyses (e.g., the Formal Safety Assessment/FSA method or statistical analysis of accident data), this research evaluates the role of key factors: Human Error, Vessel condition (Seaworthiness), Environmental conditions (Weather & Oceanography), and Regulation/Management (e.g., the role of Vessel Traffic System/VTS and Aids to Navigation). The findings will be used to formulate effective mitigation strategies to enhance maritime safety and efficiency, thereby supporting sustainable maritime development.